Screening for Fosfomycin Resistance Genes in Carbapenem- Resistant Isolates of Enterobacterales from the Bloodstream of Liver Transplant Patients - Yakup GEZER; Elif Seren TANRIVERDİ; Barış OTLU; Sezai YILMAZ; Yaşar BAYINDIR (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2022)
Introduction: Interest in fosfomycin, an old antibiotic, has been reignited because of the use of its intravenous formulation (fosfomycin sodium) in resistant infections. The aim of this study was to screen for carbapenem resistance in Enterobacterales isolates from the bloodstream, and determine the frequency of carbapenamases types and fosfomycin resistance genes in carbapenem-resistant Enterobacterales (CRE) strains. Materials and Methods: Enterobacterales isolates from the bloodstream of liver transplant patients aged 18 years and older were screened for carbapenem resistance between 2017 and 2019. In isolates that were resistant to at least one carbapenem antibiotic were further screened for fosfomycin susceptibility. Carbapenem susceptibility was tested for by the E-test, fosfomycin susceptibility was tested for by the agar dilution methods, and evaluated in accordance with European Committee on Antimicrobial Susceptibility Testing criteria. The frequency of OXA-48, NDM, KPC, VIM, and IMP type carbapenemases and fosA, fosA3, and fosC2 fosfomycin resistance genes were screened for using the polymerase chain reaction method. Results: A total of 115 Enterobacterales isolates from bloodstream infections were obtained. Carbapenem resistance was detected in 34 (29.3%) isolates, 41.2% of them were Escherichia coli and 58.8% of them were Klebsiella pneumoniae. Out of the 34 isolates, 61.8% produced carbapenemases, and OXA-48 was the most common type of carbapenemase. The fosfomycin resistance rate was 73.5%. Among the 34 carbapenem-resistant isolates, the frequency of the fosA gene was 5.9%. The genes fosA3 and fosC2 were not detected in any isolates. FosA + OXA-48 and fosA + NDM genes were detected in CRE isolates. Conclusion: This is the first study reporting on the screening for fosfomycin resistance genes in blood isolates of liver transplant patients in Turkey. Despite high fosfomycin resistance, detection of only two resistance genes reveals that there may be fosfomycin resistance due to other resistance mechanisms.